Multimodal analyses enabling artificial agents in human-machine interaction : second International Workshop, MA3HMI 2014, held in conjunction with INTERSPEECH 2014, Singapore, Singapore, September 14, 2014, Revised selected papers /: second International Workshop, MA3HMI 2014, held in conjunction with INTERSPEECH 2014, Singapore, Singapore, September 14, 2014, Revised selected papers. (2015) - Unknown
No abstract available